Rational Water and Nitrogen Management Improves Root Growth, Increases Yield and Maintains Water Use Efficiency of Cotton under Mulch Drip Irrigation - Hongzhi Zhang; Hongzhi Zhang; Aziz Khan; Daniel K. Y. Tan; Honghai Luo (Frontiers in Plant Science, 2017)
There is a need to optimize water-nitrogen (N) applications to increase seed cotton yield and water use efficiency (WUE) under a mulch drip irrigation system. This study evaluated the effects of four water regimes [moderate drip irrigation from the third-leaf to the boll-opening stage (W1), deficit drip irrigation from the third-leaf to the flowering stage and sufficient drip irrigation thereafter (W2), pre-sowing and moderate drip irrigation from the third-leaf to the boll-opening stage (W3), pre-sowing and deficit drip irrigation from the third-leaf to the flowering stage and sufficient drip irrigation thereafter (W4)] and N fertilizer at a rate of 520 kg ha-1 in two dressing ratios [7:3 (N1), 2:8 (N2)] on cotton root morpho-physiological attributes, yield, WUE and the relationship between root distribution and dry matter production. Previous investigations have shown a strong correlation between root activity and water consumption in the 40–120 cm soil layer. The W3 and especially W4 treatments significantly increased root length density (RLD), root volume density (RVD), root mass density (RMD), and root activity in the 40–120 cm soil layer. Cotton RLD, RVD, RMD was decreased by 13.1, 13.3, and 20.8%, respectively, in N2 compared with N1 at 70 days after planting (DAP) in the 0–40 cm soil layer. However, root activity in the 40–120 cm soil layer at 140 DAP was 31.6% higher in N2 than that in N1. Total RMD, RLD and root activity in the 40–120 cm soil were significantly and positively correlated with shoot dry weight. RLD and root activity in the 40–120 cm soil layer was highest in the W4N2 treatments. Therefore increased water consumption in the deep soil layers resulted in increased shoot dry weight, seed cotton yield and WUE. Our data can be used to develop a water-N management strategy for optimal cotton yield and high WUE.